JUAL BELI ONLINE DENGAN SISTEM PRE-ORDER BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Hanifah Hanifah; Ujang Hibar; Dian Samudra (Res Justitia : Jurnal Ilmu Hukum, 2023)
The development of technology and information in the era of globalization has brought enormous changes in both positive and negative terms. One of these impacts is the emergence of new electronic commerce transactions with a pre-order system. Where in these transactions between buyers and sellers do not meet each other face to face because they only use the internet as the transaction medium. In carrying out the status of the availability of the goods (stock) is not available, it does not mean empty, but the goods are only produced a little and the buyer can order them in advance with the ordering and payment system to get the goods. The research method used is normative juridical research using a state approach and an analytical approach. Sources of data in this study are secondary data sources in the form of public documents and official records (public documents and official records). In online buying and selling transactions with this pre-order system, management needs to be improved, especially in serving consumers with proof of invoices or lists from business actors to consumers.